A healthier family for life : stress-free feasts for a multi-diet family - Crous, Donna (London : Robinson, 2021)
"With A Healthier Family for Life, cooking healthy food that puts a smile on your loved ones' faces has never been easier. This book is not about the latest diet fad or trendy way of eating; it's about creating wholesome, nutritious dishes that delight the whole family without feeling restricted. Whatever diets, health conditions or food intolerances you need to cater for, this book will help your family live a happier, healthier life. Many families today have numerous health conditions and intolerances to consider, making the dinner table something of a minefield. In this gorgeous, practical book, health coach Donna Crous makes dinnertime less daunting and more healthy, with a wide range of delicious and nutritious recipes that are fully gluten-free, processed sugar-free and dairy-free, including many keto and vegan recipes. A Healthier Family for Life inspires from the very start of your day with recipes including Breakfast Toad-In-The-Hole and Silver Dollar Pancakes, through to teatime family favourites like Crumbed Chicken Tenders, Kombucha and Miso-Roasted Spare Ribs and Walnut, Kale and Cranberry-Stuffed Butternut. Donna is best known for her grain-free baking and has included recipes for Vegan Christmas Pudding and a showstopping Pear and Coffee Loaf, as well as sweet treats such as Avocado and Almond Truffles and Gut-Healing Gummies"--Publisher's description.
Ingredients for healthy eating -- Breakfasts -- Main meals -- Vegetables, salads & side dishes -- Dips, condiments & spreads -- Bakes, puddings & snacks -- Drinks.
Includes index.
Keywords: Cooking; Cuisine (Aliments naturels); Cooking (Natural foods); Cookbooks; Cookbook; cookbooks; Cookbooks; Livres de cuisine